Between concentration and pluralisation: the West German press in the 1970s - Kraiker, Christian Welfhard (2015)
The development of the West German press in the 1970s has so far been described as a transition from a period of concentration (1954-1976) to stabilisation (1976-1985). The analysis by Schütz and others has several short-comings: firstly, the argument is implicitly based on a vague empirical definition of pluralism that is understood as the number of daily newspapers with an independent editorial department in a given market. Secondly, the analysis is almost exclusively based on the daily press and ignores the impact of new journals, regional editions, weeklies, and the ‘alternative’ press on the press market of the 1970s. Finally, the turning points of 1954 and 1976 do not relate to wider changes in circulation figures and other important aspects of press history.